Indonesian EFL Students’ Writing Self-Efficacy: Inefficacious, Efficacious, and Challenges - Belladina, Cahya; Purwanti, Indah Tri; Eliwarti, Eliwarti (Indonesian Journal of Economics, Social, and Humanities, 2024)
This research aims to investigate EFL students’ writing self-efficacy at the English Study Program FKIP Universitas Riau. In this research, the researcher applied explanatory mixed method research design with a closed-ended questionnaire and an open-ended questionnaire as the instruments. The population of this research were 108 respondents from the third semester students taking Post Intermediate Reading and Writing subjects. There were two classes, consisting of 75 students, chosen as the sample in this research through cluster random sampling technique. The research findings that the third semester students’ writing self-efficacy in the English Study Program FKIP Universitas Riau is moderate, which suggests that the students’ self-belief and their judgement on their writing skills is not quite good. There are nine reasons for both of their inefficacy and their efficacy and followed by ten challenges faced by the students in writing courses. Lecturers can help students to enhance their writing self-efficacy by applying the innovative teaching strategies and students should learn more on linguistics and writing self-efficacy, practising more, reading more books, and also conducting a study group together with their friends.